Students' Mathematical Literacy in the Digital Age - Apsari Sabela; Yayu Nurhayati Rahayu; Rikrik Nurdiansyah (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study is to determine the mathematical literacy ability of students in the digital age. The method used in this research is a literature study or library research, by collecting data, reading and recording and processing research materials. The results obtained are students 'mathematical literacy level, and efforts to improve students' mathematical literacy, by applying a system of learning concept understanding and familiarizing students to solve mathematical literacy problems, then motivate students to learn more, and also facilitate student learning to learning runs more effectively